2016
DOI: 10.7554/elife.14052
|View full text |Cite
|
Sign up to set email alerts
|

A novel biosensor to study cAMP dynamics in cilia and flagella

Abstract: The cellular messenger cAMP regulates multiple cellular functions, including signaling in cilia and flagella. The cAMP dynamics in these subcellular compartments are ill-defined. We introduce a novel FRET-based cAMP biosensor with nanomolar sensitivity that is out of reach for other sensors. To measure cAMP dynamics in the sperm flagellum, we generated transgenic mice and reveal that the hitherto methods determining total cAMP levels do not reflect changes in free cAMP levels. Moreover, cAMP dynamics in the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(114 citation statements)
references
References 90 publications
(135 reference statements)
4
110
0
Order By: Relevance
“…Although these methods have yet to be implemented for mammalian sperm studies, their utility has been demonstrated in evaluations of sea urchin sperm chemotaxis and the control of flagellar movements (Solzin et al, ; Wood et al, ; Alvarez et al, ; Kashikar et al, ; Guerrero et al, ). In addition, fluorescence resonance energy transfer (FRET) has been applied to evaluate cAMP levels in the sperm flagellum in real time (Mukherjee et al, ), while optogenetics have been employed to induce cAMP synthesis by activating a light‐sensitive adenylyl cyclase in sperm (Jansen et al, ). Finally, super‐resolution microscopy has provided a view of sperm at the structural level: Recent work by Chung et al () revealed the structural organization of capacitation‐associated pathways using stochastic optical reconstruction microscopy (STORM).…”
Section: Introductionmentioning
confidence: 99%
“…Although these methods have yet to be implemented for mammalian sperm studies, their utility has been demonstrated in evaluations of sea urchin sperm chemotaxis and the control of flagellar movements (Solzin et al, ; Wood et al, ; Alvarez et al, ; Kashikar et al, ; Guerrero et al, ). In addition, fluorescence resonance energy transfer (FRET) has been applied to evaluate cAMP levels in the sperm flagellum in real time (Mukherjee et al, ), while optogenetics have been employed to induce cAMP synthesis by activating a light‐sensitive adenylyl cyclase in sperm (Jansen et al, ). Finally, super‐resolution microscopy has provided a view of sperm at the structural level: Recent work by Chung et al () revealed the structural organization of capacitation‐associated pathways using stochastic optical reconstruction microscopy (STORM).…”
Section: Introductionmentioning
confidence: 99%
“…A FRET-based cAMP sensor was used to measure the inhibition of D1R signaling by GPR88 in the cilia; however, comparisons between whole-cell and ciliary levels were not made and HH signaling was not assayed (13). A more recent study used a different FRET sensor to study cAMP, but focused mainly on cAMP in flagella (14). Three recent studies used cilia-targeted sensors to detect Ca 2+ dynamics in cilia (15)(16)(17).…”
mentioning
confidence: 99%
“…A completely novel FRET-based biosensor from the lab of Dagmar Wachten named “mlCNBD-FRET” [62] incorporates a new design built around a cyclic-nucleotide binding domain (CNBD) of a bacterial channel known as Mloti K1. This cAMP-binding fragment is sandwiched between cerulean and citrine.…”
Section: Sensors Utilizing Bacterial Camp-binding Domainsmentioning
confidence: 99%
“…Another potential cAMP microdomain of interest is the primary cilium, which contains specific adenylyl cyclases and cell surface receptors coupled to cAMP production [71] [62]. Measuring cAMP in this tiny organelle (which occupies 1/10,000 th of the cell volume) is challenging because its small size makes it difficult to optically isolate the cilium from the rest of the cell body (Figure 2).…”
Section: Using Optical Reporters To Probe Camp Microdomainsmentioning
confidence: 99%